2005
DOI: 10.1593/neo.04349
|View full text |Cite
|
Sign up to set email alerts
|

Bone Microenvironment Modulates Expression and Activity of Cathepsin B in Prostate Cancer

Abstract: Prostate cancers metastasize to bone leading to osteolysis. Here we assessed proteolysis of DQ-collagen I (a bone matrix protein) and, for comparison, DQ-collagen IV, by living human prostate carcinoma cells in vitro. Both collagens were degraded, and this degradation was reduced by inhibitors of matrix metallo, serine, and cysteine proteases. Because secretion of the cysteine protease cathepsin B is increased in human breast fibroblasts grown on collagen I gels, we analyzed cathepsin B levels and secretion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 87 publications
7
53
2
2
Order By: Relevance
“…Cathepsin B is a cysteine proteases expressed by tumor cells, which is activated in an acidic microenvironment and could participate in the vicious cycle of bone metastasis (76). It is expressed at low levels in primary prostate tumors; however, bone metastatic lesions express high levels of activated cathepsin B, suggesting that protease activity is modulated by interactions between tumor cells and the bone microenvironment (77).…”
Section: Physical Properties Of the Bone Microenvironment Hypoxiamentioning
confidence: 99%
“…Cathepsin B is a cysteine proteases expressed by tumor cells, which is activated in an acidic microenvironment and could participate in the vicious cycle of bone metastasis (76). It is expressed at low levels in primary prostate tumors; however, bone metastatic lesions express high levels of activated cathepsin B, suggesting that protease activity is modulated by interactions between tumor cells and the bone microenvironment (77).…”
Section: Physical Properties Of the Bone Microenvironment Hypoxiamentioning
confidence: 99%
“…At the same time, CTSB has been shown to play an important role in invasion and metastasis of prostate cancer (Miyake et al ., 2004). Increased CTSB expression and activity were observed in bone tissues colonized by human prostate carcinoma cells (Podgorski et al ., 2005). It was suggested that metabolically rich bone microenvironment is responsible for secretion of active CTSB from prostate cancer cells interacting with the bone (Podgorski et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Increased CTSB expression and activity were observed in bone tissues colonized by human prostate carcinoma cells (Podgorski et al ., 2005). It was suggested that metabolically rich bone microenvironment is responsible for secretion of active CTSB from prostate cancer cells interacting with the bone (Podgorski et al ., 2005). Our unpublished data also show induction of CTSB expression in prostate cancer cells, when cocultured with bone cells than when cultured alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the expression of several proteases is verified in prostate cancer cells. This increase is especially present in serine proteases, which are involved in different events of tumor establishment, such as proliferation, adhesion, migration, angiogenesis, and apoptosis (2)(3)(4)(5)(6). The tissue serine protease kallikrein 3 (also known as prostate specific antigen) plays a relevant role in this disease; prostate cancer can be diagnosed through the quantification of prostate specific antigen levels in the serum of sick individuals (7,8).…”
mentioning
confidence: 99%